PENGARUH DISIPLIN DAN PENILAIAN KINERJA TERHADAP EFEKTIVITAS KERJA PEGAWAI DI PT. PLN (PERSERO) WILAYAH SUMATERA UTARA MEDAN - Andre Fitriano (Universitas Islam Islam Sumatera Utara, 2018)
This paper is based on research at the company PT. PLN (Persero) Region of North Sumatera Medan on the influence of discipline and performance appraisal toward employees’ work attitude. This study involved all employees of the company as a population, while the sample was only 30 persons through random method. Data obtained through questionnaires was analyzed based on statistical approaches, namely multiple linear regression, t test (partial test), coefficient of determination (R²) and test f (simultaneous test) which are calculated by using SPSS program. The results of statistical process showed that the positive influence of both independent variables of discipline and performance appraisal of employee attitude even though low. This was shown through the double correlation test (R) of 0.126, so that further evaluation is needed to improve the quality of employees’ work of the company toward better performance.